2020
DOI: 10.1155/2020/8849427
|View full text |Cite|
|
Sign up to set email alerts
|

SIAT-WEXv2: A Wearable Exoskeleton for Reducing Lumbar Load during Lifting Tasks

Abstract: Lumbar Exoskeleton, as an important instance of wearable exoskeleton, has broad application prospects in logistics, construction, and other industries. Specifically, in the working scenarios that require long-term and repeated bending and rising movements, active lumbar exoskeleton (ALE) can provide effective protection and flexible assistance to wear’s waist muscles and bones, which will significantly reduce the risk of lumbar muscle strain. How to improve the human-machine coupling and enhance the assistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…To amplify human endurance while carrying heavy loads, BLEEX [ 13 ] (7-DOF/limb) was developed with intelligent and adaptable robot-based strategies where linear hydraulic actuators were used for the actuation of 4-DOF. Recently, Ji et al [ 14 ] introduced a wearable exoskeleton, SIAT-WEXv2, to support the user's waist and bones while lifting heavy objects in construction and logistic industries by providing an assistive output of 28 N.…”
Section: Introductionmentioning
confidence: 99%
“…To amplify human endurance while carrying heavy loads, BLEEX [ 13 ] (7-DOF/limb) was developed with intelligent and adaptable robot-based strategies where linear hydraulic actuators were used for the actuation of 4-DOF. Recently, Ji et al [ 14 ] introduced a wearable exoskeleton, SIAT-WEXv2, to support the user's waist and bones while lifting heavy objects in construction and logistic industries by providing an assistive output of 28 N.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the number of subjects in this study is the same as those in references [ 5 , 27 ] and higher than those in some previous researches such as [ 28 , 30 ], but more subjects, including female subjects, should be involved in the experiment in order to obtain more reliable results in the future.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that exoskeletons have positive results in the biomechanical evaluation. It has been proven to significantly reduce the muscle activity of the main muscles involved in handling or overhead work [ 27 , 28 ]. The passive back exoskeleton has been shown to reduce spinal muscle activity by 20 to 25% in real car assembly operations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…During long-term lifting activity, the exoskeleton is reported to decrease stress and lumbar muscle strain. In the updated model SIAT-WEXv2, a 48% reduction of muscle activity of Lumbar erector spinae was achieved (Ji et al, 2020).…”
Section: Active Back-support Devicesmentioning
confidence: 99%